Seroprevalence of Toxocariasis and Its Associated Risk Factors among Adult Population in Kavar District, Fars Province, South of Iran: A Cross-Sectional Community-Based Seroepidemiological Survey - Fatemehsadat Pezeshkian; Ali Pouryousef; Mostafa Omidian; Fattaneh Mikaeili; Ali Reza Safarpour; Sara Shojaei-Zarghani; Bahador Sarkari (Interdisciplinary Perspectives on Infectious Diseases, 2023)
Toxocariasis as a common neglected disease is the culprit of infecting all age groups. The current cross-sectional study was designed to assess the seroprevalence of toxocariasis and risk factors associated with seropositivity of Toxocara infection among the general population of adults in the Kavar district, south of Iran. A total of 1060 participants with an age range of 35 to 70 years from the Kavar region entered the study. Manual ELISA was utilized to detect anti-Toxocara-specific antibodies in their serum samples. In addition, demographic information as well as risk factors related to toxocariasis was collected from individuals who participated in the survey. The mean age of the participants was 48.9 (±7.9) years old. Out of 1060 subjects, 532 (50.2%) were men, and 528 (49.8%) were women. The overall Toxocara seroprevalence was 5.8% (61/1060). The prevalence of Toxocara seropositive cases was significantly different between males and females (p = 0.023). The seropositive rate for Toxocara infection was also significantly higher in housewives (p = 0.003) and subjects with learning disabilities (p = 0.008). Multivariable logistic regression revealed that housewives (OR = 2.04, 95% CI: 1.18–3.51, p = 0.010) and subjects with learning disability (OR = 3.32, 95% CI: 1.29–8.52, p = 0.013) were at increased risk of Toxocara infection. The findings of the current study depicted a noticeable seroprevalence of Toxocara infection in the general population in the Kavar district, southern Iran. An increased risk of toxocariasis has been associated with learning disabilities and being a housewife. All of the toxocariasis-positive cases had contact with animals, at some point in their life. In perspective, it is necessary to raise awareness of this infection among the population while surveilling Toxocara infection in high-risk groups.